Statement by the Hungarian Ministry of Foreign Affairs Referring to the Report of the Special Committee on Hungary - Héderváry, Claire de (1957)
Records of this digital collection were assembled to document the work of the UN Special Committee on the Problem of Hungary established on January 10, 1957 by the United Nations General Assembly for the purpose of investigating the 1956 Hungarian revolution. Non-official English translation of the statement.